The Concubine - Amadi, Elechi (Nigeria, 1966)
Ihuoma, a beautiful young widow of exemplary character, has the admiration of the entire community in which she lives, and especially of the hunter Ekwueme. Obedient to the expectations of the traditional society they belong to, they forswear their love so that Ekwueme can marry the girl whom he has been betrothed since birth...
Keywords: Fiction